2006
DOI: 10.1080/07357900600705284
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of Knowledge, Experiences, and Preferences for Disclosure of Diagnosis and Prognosis between Terminally-Ill Cancer Patients and Their Family Caregivers in Taiwan

Abstract: The arguments that cancer patients from an Asian culture (i.e., Chinese/Taiwanese culture) have different preferences regarding being informed of their diagnosis and prognosis and that family members have legitimate superior power in decision making could not be supported by data from this group of terminally-ill cancer patients. Physicians need to respect patients' preferences rather than routinely taking the family's opinions into consideration first in the event of disagreement. Equipped with adequate infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 44 publications
0
96
1
6
Order By: Relevance
“…This is in contrast with the general perception that Asian patients should be protected from being given bad news, for fear that they would not be able to cope (Huang et al, 1999;Lapine et al, 2001). However, many studies have shown that the reverse is often true (Kumar et al, 2004;Tang et al, 2006). Honesty is an important characteristic in order for the patient to trust their doctors (Nguyen and Bellamy 2006).…”
Section: Discussioncontrasting
confidence: 42%
“…This is in contrast with the general perception that Asian patients should be protected from being given bad news, for fear that they would not be able to cope (Huang et al, 1999;Lapine et al, 2001). However, many studies have shown that the reverse is often true (Kumar et al, 2004;Tang et al, 2006). Honesty is an important characteristic in order for the patient to trust their doctors (Nguyen and Bellamy 2006).…”
Section: Discussioncontrasting
confidence: 42%
“…Physicians consistently overestimated prognosis by at least 30% [41]; their estimate of survival could be divided by 3.5 for actual survival [42]. In a previous study, fewer than one third of adult Taiwanese patients with terminal cancer and approximately half of their families reported that health care personnel had informed them about the prognosis and discussed the goals of future care [43]. The decision to begin palliative chemotherapy should not end the decision-making process, especially when that decision was made several months earlier [14,44].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The aggressiveness of EOL care increased over the 3 years studied, as did the health care costs in Taiwan [38]. The present study shows that 81% of Taiwanese working-age terminal cancer patients between 2009 and 2011 experienced some form of aggressive EOL care.The rates of more than 14 days ofhospitalization anddyingin an acute-care hospital were high.It has been reported that less than one-third of adult Taiwanese terminal cancer patients and approximately half of their families reported that the health care professionals had informed them about the prognosis and discussed the goals of future care with them [45]. In addition, only one in six Taiwanese cancer patients use hospice care in their last year of life [46].…”
Section: Resultsmentioning
confidence: 99%